EVALUASI KEBIJAKAN KETERTIBAN UMUM DI KOTA PALU (Studi Kasus Perda Nomor 21 Tahun 1998 Tentang Larangan Perbuatan Prostitusi dan Praktik Tuna Susila dalam Wilayah Kotamadya Palu) - Syamsuddin, Syamsuddin (Katalogis, 2017)
The purpose of this research was to reveal the evaluation of prostitution control in Palu based on the Local Regulation Number 21, 1998, and to find out the inhibiting and supporting factors of the growing prostitution practices in Palu based on the policy evaluation model by William N Dunn using these aspects: 1) effectiveness, 2) efficiency, 3) Adequateness, 4) Equality, 5) Responsiveness, and 6) Precision. This is a qualitative research. There were 7 informants taken purposively. These research shows that the implementation of the local regulation number 21, 1998 concerning the prohibition of prostitution acts and practices in Palu City was not optimal due to the fact that: 1) the team intended to control the prostitution did not work effectively, 2) the control of prostitution was not fair because of only focusing on prostitutes, not controlling the prostitution-related workers such as pimps and others. The inhibiting factors have made it less optimal such as the personnel was not strict in providing the punishment, the police persons and the city guards were not serious in doing theirs jobs and operational cost was insufficient.